Implementasi Model Pembelajaran Jigsaw Dalam Meningkatkan Kerjasama Antar Siswa Di MA Asy-Syari’ah - Rima Erviana; Siti Qomariyah; Siti Nurafifah; Najrul Jimatul Rizki; Neneng Neneng (Jurnal Budi Pekerti Agama Islam, 2024)
Education serves as a crucial foundation for fostering collaborative skills among students, particularly in subjects requiring in-depth understanding such as mathematics. This research aims to investigate the impact of implementing the Jigsaw Learning Model in enhancing the level of collaboration among students in the context of mathematics learning. The Jigsaw Learning Model, introduced by Aronson and Patnoe (2011), emphasizes collaboration and active involvement of students. This method involves collaborative learning where each student is responsible for a portion of the learning material and must collaborate with their peers to comprehend the entire concept. This study explores the effectiveness of this model in improving collaboration among students in mathematics learning. Through an experimental research design, data is collected through classroom observations, interviews, and document. Data analysis is conducted to measure changes in the level of student participation, understanding of mathematical concepts, and their perceptions of collaborative learning. The results of this research are expected to provide valuable insights for educational practitioners and researchers regarding the potential of the Jigsaw Learning Model in enhancing student collaboration in the context of mathematics learning.